Irrigated‐tip catheters for radiofrequency ablation of right‐sided accessory pathways in adolescents. Issue 10 (27th September 2017) - Telishevska, Marta; Faelchle, Johannes; Buiatti, Alessandra; Busch, Sonia; Reents, Tilko; Bourier, Felix; Semmler, Verena; Kaess, Bernhard; Horndasch, Michaela; Kornmayer, Marielouise; Kottmaier, Marc; Deisenhofer, Isabel; et al.
Abstract: Background: Catheter ablation of right‐sided accessory pathways (APs) has lower success and higher recurrence rates compared to left‐sided substrates. Irrigated‐tip catheter (ITC) ablation might offer an advantage in this setting but data about its use in patients below 18 years are scarce. The aim of this study was to compare an ITC approach to conventional catheter ablation. Methods: A retrospective analysis of all patients <18 years undergoing radiofrequency ablation (RFA) for right‐sided APs from 2004 to 2014 at our institution was performed. Patients either underwent an ITC approach in combination with 3‐D mapping (Group 1; n  =  53) or a conventional non‐ITC approach (Group 2; n  =  52). Study endpoints were acute procedural success, safety, and recurrence rate. A total of 105 mostly adolescent patients (56.2% male; median age 14 years) with 107 right‐sided APs were included. Results: The prevailing anatomic AP locations were right posteroseptal (44.9%), right anterior/anterolateral (24.3%), and right lateral (13.1%). Acute success (94.3% vs 94.2%) did not differ between the groups. One major complication (pericardial effusion) occurred in the non‐ITC group. Overall, freedom from AP recurrence was 94% at 4 years in the ITC group, and 81% at 4 years in the non‐ITC group (P  =  0.04). Conclusions: The use of ITCs in combination with 3‐D mapping system for ablation of right‐sided APs in adolescents has a high acute success rate, is safe, and associated with a significantly reduced recurrence rate compared to a non‐ITC/conventional approach. It might be considered as alternative approach in this age group.